2020
DOI: 10.1186/s12966-020-01013-7
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the use and reporting of evaluation frameworks within evaluations of physical activity interventions

Abstract: Background Evaluation of physical activity interventions is vital to inform, and justify, evidence-based policy and practice to support population-wide changes in physical activity. Several evaluation frameworks and guidance documents have been developed to facilitate the evaluation and reporting of evaluation studies in public health. However, there is a lack of evidence about whether frameworks are being used to guide evaluation. There continues to be claims of poor and inconsistent reporting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 108 publications
0
14
0
Order By: Relevance
“…This may be particularly important within multi-project programmes like GHGA, which are designed and funded nationally but delivered and evaluated through local projects. We have previously argued that appropriate use of an evaluation framework to guide evaluation and reporting can improve the quality of an evaluation study [28]. Use of a framework can also facilitate identification and agreement of evaluation objectives and methods between stakeholders [71].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be particularly important within multi-project programmes like GHGA, which are designed and funded nationally but delivered and evaluated through local projects. We have previously argued that appropriate use of an evaluation framework to guide evaluation and reporting can improve the quality of an evaluation study [28]. Use of a framework can also facilitate identification and agreement of evaluation objectives and methods between stakeholders [71].…”
Section: Discussionmentioning
confidence: 99%
“…The application of frameworks and logic models are now commonly recommended to guide the evaluation and reporting of physical activity interventions. However, our own systematic review of evaluation frameworks showed limited use and/or reporting of frameworks in evaluation studies of physical activity interventions [28]. The reasons for this remain unclear.…”
Section: Introductionmentioning
confidence: 96%
“…When evaluating such processes, logic models are a valuable first step, describing the potential mechanisms of how a programme works [ 46 , 47 ]. Moreover, they have recently been identified as a potential framework for the evaluation of PA interventions in a systematic review by Fynn et al [ 44 ]. In the present study, we developed a logic model to illustrate the planned activities and expected effects within the PArC-AVE Project and, in the next step, to guide the evaluation of CP and its determinants (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Following calls for more precise reporting of such studies (e.g. [ 29 , 38 , 43 , 44 ]), we provide a thorough description of the activities that were undertaken, the underlying programme logic, and the evaluation design. Ultimately, this study will help to increase the knowledge base of co-creation strategies in the field of PA promotion and to foster their scientific as well as practical advancement.…”
Section: Introductionmentioning
confidence: 99%
“…Following calls for more precise reporting of such studies (e.g. [29,38,43,44]), we provide a thorough description of the activities that were undertaken, the underlying programme logic, and the evaluation design. Ultimately, this study will help to increase the knowledge base of co-creation strategies in the eld of PA promotion and to foster their scienti c as well as practical advancement.…”
mentioning
confidence: 99%